Exploring Care Management for Older Adults with Illnesses as Family Members’ Responsibility. The Need for Social Workers’ Support Services in Nigeria - Ene, Jacinta Chibuzor; Chukwu, Ngozi Eucharia; Ajibo, Henry Tochukwu (European Journal of Mental Health, 2022)
Introduction: Aging oftentimes comes with health-related issues. Usually, family members are obliged to provide care management for older adults. They must perform this task despite their limited knowledge of their patients’ health conditions. Hence, securing care management for older adults with illnesses becomes a dilemma for consideration. Aims: Older adults require support in managing health conditions. This study hopes to promote the following: First, provide understanding of how family members perceive caregiving. Second, provide insight into family members’ management of health care challenges. Third, explore the need for geriatric support services in providing care for older adults. Methods: The study employed a qualitative research method. Focus Group Discussion was utilized to elicit data from 24 participants admitted to four health care facilities at Enugu-North, Nigeria. Results: Findings indicated that participants perceived care management for the older adults as a filial responsibility that should be provided till their demise. However, the majority experienced difficulties to this effect, other major concerns found include age and the older adult’s attitude, financial challenges, the changing contemporary society, and caregiving stress due to the care recipient’s health status. While many of the participants indicated a preference for traditional medicine as an alternative to rapidly increasing health service charges owing to lagging geriatric support; others were less reliant on the governmental welfare support services. Conclusions: With the government implementing aging and health care policies, Non-Governmental Organizations (NGOs) and Civil Society Organizations (CSOs) in collaboration with geriatric social workers can help develop care-aid programs for older adults’ healthy wellbeing.